(untitled) (diségno, 2021)
The event presented by the Department of History, Design and Restoration of Architecture of Sapienza University of Rome, and sponsored by UID Unione Italiana per il Disegno [1], is a moment of exchange and scientific and cultural update; the event is in its third edition after the previous editions held at the University of Pavia and the Politecnico di Torino (read more).